Więziotwórcze funkcje chleba w obozie koncentracyjnym - Posłuszny, Łukasz (My University, 2014)
The article follows the multiple functions bread had in life of concentration camp prisoners. At first a short history of bread in European culture is drawn to visualize the immense panorama of places bread appears, but at the same time a key part it plays in cultural and social processes until now. In the second part focus of interest moves to hunger context of concentration camp bread appears in. Its function as a tool of social control and objectification within the framework of Erving Goffman Total institution theory is juxtaposed with various subjectivizing forms bread morphs into when manipulated by prisoners. It provokes creation of material and non-material culture on the one hand, and specific social bonds on the other hand, which try to be partially explained by mechanisms named in Peter Blau’s exchange theory
Keywords: Kultura materialna; holokaust; rzeczy; materialność; jedzenie; chleb; obóz koncentracyjny; instytucja totalna; Goffman